WAKAF DAN PENDIDIKAN ISLAM KLASIK - Harahap, Muhammad Yunan (Jurnal Ilmiah Al-Hadi; Vol 2 No 2 (2017): JURNAL Ilmiah AL-HADI, 2018)
This paper examines how the role of wakaf in the classical Islamic era plays an important role and great influence on the development of science at that time. The role of waqfs had a tremendous impact on the birth of scientists at the time. The purpose of this paper is to explore more deeply how the role of waqf in classical Islamic education, so that people in general are not focused on the traditional waqf who assume wakaf just a mosque, cemetery and other places of worship where the benefitsareverylimited but more than that The benefit of wakaf canbe moreextensive if managed more productively as exemplified by our previous scholars. The method in this paper is through literature study where the authors collect data from various sources and then in the description to get the maximum results. The implication of this paper is the prospect of waqf in Islamic education is very positive, if the community especially in Indonesia supports with the change of mindset towards the function of waqf which has been limited to the matter of worship only.And must be professionally managed in the framework of the future progress of Islamic education.